Thumb CMCJ prosthetic total joint replacement: a systematic review. Issue 5 (4th May 2021) - Holme, Thomas J.; Karbowiak, Marta; Clements, Jennifer; Sharma, Ritesh; Craik, Johnathan; Ellahee, Najab
Abstract : Thumb carpometacarpal joint (CMCJ) arthritis is a common and painful condition. Thumb CMCJ prosthetic replacement aims to restore thumb biomechanics and improve pain and function. Early reviews demonstrated a lack of high-quality studies, but more recently a significant number of higher-quality studies have been published. This review provides a concise and systematic overview of the evidence to date. A systematic review of several databases was conducted according to PRISMA guidelines. Studies evaluating the outcomes of thumb CMCJ prosthetic total joint replacement were included. Data extracted included patient-reported outcome measures (PROMs), pain scores, range of motion, strength, survival rates and complications. A total of 56 studies met all inclusion criteria and were analysed. There was one randomized controlled trial, three prospective comparative cohort studies, five retrospective comparative cohort studies, and 47 descriptive cohort studies. The reported studies included 2731 patients with 3048 thumb total CMCJ prosthetic joint replacements. Follow up ranged from 12 months to 13.1 years. In general, good results were demonstrated, with improvements in PROMs, pain scores and strength. Failure rates ranged from 2.6% to 19.9% depending upon implant studied. Comparative studies demonstrated promising results for replacement when compared to resection arthroplasty, with modest improvements in PROMs but at a cost of increased rates of complications. Studies reporting outcomes in thumb CMCJ prosthetic total joint replacement are increasing in both number and quality. Failure, in terms of loosening and dislocation, remains a concern, although in the medium-term follow up for modern implants this issue appears to be lower when compared to their predecessors. Functional outcomes also look promising compared to resection arthroplasty, but further high-quality studies utilizing a standardized resection arthroplasty technique and modern implants, together with standardized core outcome sets, will be of value. Cite this article: EFORT Open Rev 2021;6:316-330. DOI: 10.1302/2058-5241.6.200152